National Medical Expenditure Survey, 1987: Household Survey, Expenditures, Sources of Payment, and Population Data (Public Use Tape 18) ([Verlag nicht ermittelbar], 1994)
The National Medical Expenditure Survey (NMES) series provides information on health expenditures by or on behalf of families and individuals, the financing of these expenditures, and each person's use of services. The Household Survey was fielded over four rounds of personal and telephone interviews at four-month intervals. Baseline data on household composition, employment, and insurance characteristics were updated each quarter, and information on all uses of and expenditures for health care services and sources of payment was obtained. In addition to the core data, Public Use Tape 18 provides supplemental information on income, assets, and taxes. Income-related variables distinguish among 26 types of income. Also included are demographic characteristics of respondents (age, race/ethnicity, sex), tax filing status, home ownership, type of occupation, medical deductions, type of payment for health care, day care arrangements for children, pregnancies during 1987, related prenatal care, veteran status, and loss of a close relative or friend.